Photoreactions of cyclic sulfite esters: Evidence for diradical intermediates - White, Rick C.; Arney, Benny E., Jr.; Ihmels, Heiko (Beilstein Journal of Organic Chemistry, 2012)
The photochemistry of a phenyl and 1,2-diphenyl substituted sulfite ester is reported. The performance of photoreactions under relatively mild reaction conditions enables the detection of products that have not been observed in previous studies. It is concluded that, complementary to the initially proposed carbene intermediates, diradicals may also be considered.
Keywords: diradicals; mechanisms; photochemistry